Pesona Form Driven dari Tipografi pada Kemasan Makanan dan Minuman - Julianto Julianto (Bina Nusantara University, 2010)
Letters or widely known in the designer community design as typography, is the most essential design element, because it has a double function, as both the language of verbal and also visual language. Its presence in the design world often dominates the portion of the design. It is also often evident in many information media, and capable of persuading its audience through the enchanting beauty (form driven), both types of letter itself and its well-ordered structure, designed by a designer. This also occur in food and beverage packaging, which when people make very careful decisions, since it involves preferences or consumption of their own choice, is an added value if their favorite food/drink is packed with a cool typography design.